2001
DOI: 10.1097/00002030-200105040-00009
|View full text |Cite
|
Sign up to set email alerts
|

HIV infection among youth in a South African mining town is associated with herpes simplex virus-2 seropositivity and sexual behaviour

Abstract: HIV infection among young women increases rapidly after the onset of sexual activity and reaches extremely high levels by 24 years of age. These findings suggest that rates of HIV transmission from men to women are high and that HSV-2 plays a major role in the spread of HIV in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
118
2
2

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(132 citation statements)
references
References 32 publications
7
118
2
2
Order By: Relevance
“…[28][29][30][31] The questionnaire was reviewed by experts on HIV and reproductive health surveys, both in South Africa and internationally, and was extensively piloted. 32 Throughout the survey, "sex" was defined as vaginal or anal intercourse and "sexual experience" was defined as having had vaginal or anal intercourse.…”
Section: Methodsmentioning
confidence: 99%
“…[28][29][30][31] The questionnaire was reviewed by experts on HIV and reproductive health surveys, both in South Africa and internationally, and was extensively piloted. 32 Throughout the survey, "sex" was defined as vaginal or anal intercourse and "sexual experience" was defined as having had vaginal or anal intercourse.…”
Section: Methodsmentioning
confidence: 99%
“…Among young adults 15± 24 years old in Tanzania, a 1995 study found HIV prevalence of 5.6% among men and 3.6% among women who did not report any lifetime sexual activity vs 4.8% and 12% for men and women reporting one or more sexual partners 51 . In a 1999 study in South Africa, 6.8% of women and 1.2% of men 14± 24 years old who reported never having sex were HIV positive; however, a validation study found some under-reporting of sexual activity 52 . In a case± control study in Uganda, in two of seven cases with only one lifetime sexual partner, the partner was HIV-negative, three were HIVpositive, and two others not tested 53 .…”
Section: Adult Hiv Without Sexual Exposure To Hivmentioning
confidence: 95%
“…Numerous studies demonstrated that sexually transmitted infections (STIs) enhance susceptibility to HIV-1 acquisition and transmission, even in the absence of clinical symptoms (1)(2)(3)(4)(5). The most common viral STI acquired during sexual contact in the developing world is genital herpes (6), which is primarily caused by HSV type 2 (HSV-2), although HSV type 1 infection can also lead to genital herpes (7).…”
mentioning
confidence: 99%
“…The most common viral STI acquired during sexual contact in the developing world is genital herpes (6), which is primarily caused by HSV type 2 (HSV-2), although HSV type 1 infection can also lead to genital herpes (7). Pre-existing HSV-2 infection is a risk factor for acquiring HIV-1 infection through sexual contact (1)(2)(3)(4). Although it remains unclear how HSV-2 enhances HIV-1 susceptibility, several mechanisms have been proposed.…”
mentioning
confidence: 99%